O sistema LANDSAT com ênfase no sensor Thematic Mapper (TM) - Hartmann, Carlos; Adornes , Andréa; Harkot, Paulo (Sociedade & Natureza, 1989)
O sistema LANDSAT com ênfase no sensor Thematic Mapper (TM)